Sourcing and pricing strategies for two retailers in a decentralized supply chain system under supply disruption - M.A. Azarmehr; S. Rezapour; R. Tavakkoli-Moghaddam (Management Science Letters, 2012)
This paper presents the decentralized supply chain with two suppliers and two competing retailers. It also investigates the sourcing and pricing strategies of two retailers in a decentralized supply chain system under a supply disruption environment. These retailers face their individual stochastic demand markets; however, they compete with each other through a two-stage price and service operation. The interactive dynamics among retailers is characterized, including the existence and uniqueness of the Nash Equilibrium in service and price games demonstrated.